PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP MARKETING AGENSI YANG BEKERJASAMA DENGAN BRAND PELAKU MISLEADING ADVERTISING - Akdavi Akbar Faruq (2023)
In the development of the national economy in the midst of the fast-moving era of globalization, many service providers have emerged whose scope is related to the rapid development of technology. This is closely related to the process of distributing products originating from business actors to their consumers. In this process a means is needed to convey information about the product, the means is through marketing and advertising. However, in reality, many of the advertisements that are displayed do not display normative characteristics that should explain in depth about a product. This study aims to analyze the law of protection for consumers from marketing agencies that work with misleading advertisers brands. The research method used is normative juridical using a statutory approach. The legal materials analyzed are Law Number 8 of 1999 concerning Consumer Protection, Law Number 32 of 2002 concerning Broadcasting, and other related laws. The results of this study explain that there is still no law that specifically regulates advertising and regulates the rights and responsibilities of business actors in the field of advertising. This research is expected to provide benefits for parties such as marketing agencies, brands (business actors), and the government to policy makers.